2017
DOI: 10.1371/journal.ppat.1006628
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1 alpha as a therapeutic target for primary effusion lymphoma

Abstract: Primary effusion lymphoma (PEL) is an aggressive B-cell lymphoma with poor prognosis caused by Kaposi’s sarcoma-associated herpesvirus (KSHV). Previous studies have revealed that HIF-1α, which mediates much of the cellular response to hypoxia, plays an important role in life cycle of KSHV. KSHV infection promotes HIF-1α activity, and several KSHV genes are in turn activated by HIF-1α. In this study, we investigated the effects of knocking down HIF-1α in PELs. We observed that HIF-1α knockdown in each of two PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…This sheds the light on the potential therapeutic targeting of HIF-1α in the context of KSHV-induced PEL as HIF-1α activity is stimulated by KSHV infection and HIF-1α activates numerous KSHV genes. This is reinforced by the fact that HIF-1α suppression was associated with a significant inhibition of PEL growth and a reduction in the activation of KSHV lytic and latent genes ( 181 ). In addition, HBV HBx interferes with HIF-1α protein degradation ( 182 ) and enhances its synthesis ( 183 ).…”
Section: Introductionmentioning
confidence: 99%
“…This sheds the light on the potential therapeutic targeting of HIF-1α in the context of KSHV-induced PEL as HIF-1α activity is stimulated by KSHV infection and HIF-1α activates numerous KSHV genes. This is reinforced by the fact that HIF-1α suppression was associated with a significant inhibition of PEL growth and a reduction in the activation of KSHV lytic and latent genes ( 181 ). In addition, HBV HBx interferes with HIF-1α protein degradation ( 182 ) and enhances its synthesis ( 183 ).…”
Section: Introductionmentioning
confidence: 99%
“…Later during lytic replication, the ORF34 lytic protein binds and stabilizes HIF-2α [45], which could promote eIF4E2-dependent translation [27]. Interestingly, HIF-1α is required for normal lytic gene expression during normoxia in both KSHV and murine gammaherpesvirus 68 infections [46,47]. In our experiments, the differential effects of eIF4E2 silencing on PEL proliferation suggests that KSHV latency does not fully recapitulate a hypoxic phenotype and suggests that KSHV selectively accesses the hypoxic gene expression program.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, studies in primary effusion lymphoma (PEL) cells, revealed that knockdown of HIF-1␣ in PEL lines led to reduction in both aerobic and anaerobic glycolysis as well as lipid biogenesis, suggesting that it is necessary for maintaining an optimal metabolic state for PEL growth (20). Interestingly, HIF-1␣ suppression led to a reduction in the activation of lytic KSHV genes and a decrease in the expression of KSHV latent genes, including those encoding LANA, vCycline, and kaposin, under both hypoxic and normoxic conditions (20).…”
Section: Discussionmentioning
confidence: 99%